Consumer financial dispute resolution in a comparative context : principles, systems and practice / Shahla F. Ali. - Ali, Shahla F. (Cambridge University Press, 2013)
Nearly all major global financial centres have developed systems of consumer financial dispute resolution. Such systems aim to assist parties to resolve a growing number of monetary disputes with financial institutions. How governments and self-regulatory organizations design and administer financial dispute resolution mechanisms in the context of increasingly turbulent financial markets is a new area for research and practice. Consumer Financial Dispute Resolution in a Comparative Context presents comparative research about the development and design of these mechanisms in East Asia, North America and Europe. Using a comparative methodology and drawing on empirical findings from a multi-jurisdictional survey, Shahla Ali examines the emergence of global principles that influence the design of financial dispute resolution models, considers the structural variations between the ombuds and arbitration systems and offers practical proposals for reform.